Experimental investigation of the effect of thermal cycling on the thermomechanical properties of three rock varieties for high temperature thermal energy storage. Issue 1 (1st January 2023) - Fränzer, S; Jeskulke, J; Neumann, K M; Schumski, S; Thomas, S L; Duda, M; Witte, L C; Brajer, C; Backers, T
Abstract: During the past years "rock batteries" have become increasingly relevant for the storage of renewable energy sources, such as wind and solar energy, because of their economic and ecological advantages with respect to previously more common materials for thermal energy storage (TES) such as salt. In rock-based TES systems, thermal energy is stored in packed-bed rock using air as heat transfer fluid. We investigated three different rock types with respect to changes in thermomechanical properties after different numbers of thermal cycles, Ruhr sandstone (Oberste quarry in Dortmund - Germany), basalt (commercial MTV basalt) and Calanca gneiss. Cylindrical samples were heated to 800°C within 11, 5 h before temperature was kept constant for another 30 min and then decreased within 11, 5 h. Samples were thermomechanically investigated before thermal treatment, and again after 1, 3, 7 and 15 cycles. Additionally, two samples of each rock type were subjected to a thermal cycle with a maximum temperature of 450°C and to 1000°C, respectively, at a heating/cooling rate corresponding to that of the samples heated to 800°C. Samples were characterised with respect to ultrasound wave velocity, bulk density, thermal conductivity, thermal diffusivity, uniaxial compressive strength, splitting tensile strength, mineral content (X-ray powder diffraction) and microstructure (thin section analysis). Samples of basalt could not withstand the standard heating rate. The samples crushed into small pieces also when heating rates were reduced and at a maximum heating temperature of 800°C. For sandstone and gneiss, the ultrasound wave velocity, bulk density, thermal conductivity, thermal diffusivity, uniaxial compressive strength and splitting tensile strength decreased systematically with increasing number of cycles, while the maximum reduction occurred after the first cycle and the relative reduction was similar between both rocks. Microstructural analysis indicated an increase in crack density and minor mineralogical changes upon heating. Both rocks, Ruhr sandstone and Calanca gneiss, appear suitable for TES, but Calanca gneiss is less suitable for temperatures above 800°C due to a significant reduction in bulk density and uniaxial compressive strength when heated to 1000°C. Also, its anisotropy and anisotropic response to heating can lead to preferred flow paths of the heat transfer fluid. Ruhr sandstone maintains a high uniaxial compressive strength of about 100 MPa even after 15 cycles while thermal capacity was only slightly reduced or even increased, and can be recommended for use in high temperature TES. This study is the outcome of a research-oriented teaching program at Ruhr-University Bochum within the Geoscience curriculum for students with focus on Engineering Geology. Student authors (Fränzer to Thomas) are listed in alphabetical order.